Effect of Laser Shock Peening on the Microstructures and Properties of Oxide‐Dispersion‐Strengthened Austenitic Steels. Issue 3 (7th November 2017) - Yan, Xueliang; Wang, Fei; Deng, Leimin; Zhang, Chenfei; Lu, Yongfeng; Nastasi, Michael; Kirk, Marquis A.; Li, Meimei; Cui, Bai
Abstract : Oxide‐dispersion‐strengthened (ODS) austenitic steels are promising materials for next‐generation fossil and nuclear energy systems. In this study, laser shock peening (LSP) has been applied to ODS 304 austenitic steels, during which a high density of dislocations, stacking faults, and deformation twins are generated in the near surface of the material due to the interaction of laser‐driven shock waves and the austenitic steel matrix. The dispersion particles impede the propagation of dislocations. The compressive residual stress generated by LSP increases with successive LSP scans and decreases along the depth, with a maximum value of −369 MPa. The hardness on the surface can be improved by 12% using LSP. In situ transmission electron microscopy (TEM) irradiation studies reveal that dislocations and incoherent twin boundaries induced by LSP serve as effective sinks to annihilate irradiation defects. These findings suggest that LSP can improve the mechanical properties and irradiation resistance of ODS austenitic steels in nuclear reactor environments. Abstract : Laser shock peening (LSP) has been applied to oxide‐dispersion‐strengthened (ODS) austenitic steels in order to improve the mechanical properties and irradiation resistance. Significant plastic deformation and compressive residual stress are generated by LSP in the near surface, improving the hardness. Dislocations and incoherent twin boundaries induced by LSP can serve as effective sinks to annihilate irradiation defects.